Constructability of offshore construction project using cost significant method - Okvianto, Rico. (2008)
This dissertation reviews the application of cost-significant method in estimating and pricing an offshore platform in a certain location. It explains how the principle of cost-significance can lead to a simplified method of pricing and controlling development of an offshore platform. Two cost models are developed using data from 4 past projects in one location and 2 past projects in other location. The first cost model derived from the analysis is used to test the cost of a future repeat in the same location. The test result is encouraging as the first step to explore the refinement of application of cost-significant method for other offshore projects in other locations as well as to support concurrent planning in achieving overall cost effectiveness.